The readiness of a student for constructive social interaction in relation to life safety - Leshchynska, Olena A.; Firman, Volodymyr M.; Marych, Volodymyr M.; Ilchyshyn, Yaroslav V.; Velykyi, Yarema B. (Linguistics and Culture Review, 2021)
One of the most important things about life safety is the implementation of appropriate means and measures to create and maintain healthy and safe living conditions and human activities both in everyday life and during emergencies. The human factor as a factor in life safety can be the main source of danger. A person’s readiness for responsible constructive behaviour is formed due to the influence of organisational culture of the enterprise, as well as information space. The authors aimed to investigate the role of moral attitudes of young people and their readiness for constructive social interaction. The study took place in the 2019-2020 academic year at Lviv Polytechnic National University. The empirical study involved 535 students. The questionnaire was carried out. Factor analysis identified six factors. It was established that most students have consumeristic, authoritarian and destructive ideas, therefore their reactions to the actions of life safety specialists aimed at introducing labour safety technologies are reduced to formal observation.